Facilitating scholarly publication:genre characteristics of English research article introductions and methods - Budsaba Kanoksilapatham, (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2012)
This article acknowledges the increasingly important role of research articles (RAs) written in English. To enable scholars who are not competent in English to compete with others academically, this study provides a detailed description of the English empirical RA Introductions and Methods. A dataset of 60 RAs representing top quality journals in biomedical engineering was compiled and subsequently divided into four sub-datasets representing the four major sections. The Introduction and Methods sub-datasets were analysed by genre analysis into ‘moves’ and ‘steps’. Then, the linguistic features pervasive and salient in individual move or step instances were identified. The analysis revealed that each section displayed a schematic structure, consisting of a set of moves and steps. In addition, clusters of lexico-grammatical features associated with a communicative function were identified. This two-tier genre analysis suggests that the structural patterns and linguistic features interact with each other functionally. The findings are pedagogically useful in developing genre competence for scholars to better access the content they need from RAs and to effectively disseminate their achievements in their respective fields.